Diversity, density and distribution of termites in housing complexes in Purwokerto, Central Java, Indonesia - Hery Pratiknyo; TRISNO HARYANTO; DWI NURCAHYO APRIYANTO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pratikno H, Haryanto T, Apriyanto DN. 2020. Diversity, density, and distribution of termites in housing complexes in Purwokerto City, Central Java Indonesia. Biodiversitas 21: 5729-5735. Termite attacks have detrimental effects on buildings and incur considerable costs. The rapid development of housing complex in Purwokerto City, Central Java Province, Indonesia urges an investigation on the occurrence of termite attacks. This research aimed to identify the diversity of termite species, its spatial distribution and its density on a variety of wood on housing complexes in Purwokerto City and the surrounding areas. The context of this study focused on wood species commonly used by the developers, namely albasia (Paraserianthes falcataria), which is commonly used for the upper ceiling, bangkirai (Shorea laevifolia) for poles and door/window frames, and teak (Tectona grandis) which is often used for door and window boards. We used bait techniques with the rationale that it is cheap and environmentally friendly as well as accurate. Four housing complexes in four subdistricts were randomly selected stratified based on four altitude ranges (<100 m, 100 m, 200 m, and 300 m). In each selected housing complex wood baits of three durability types (i.e. albasia, bangkirai and teak) were installed, each measuring 30 cm x 2 cm x 2 cm with five replications. Data of termite species, spatial distribution of termite species, and individual density in each housing complex were recorded after three months since the wood baits were stockpiled. Microclimate variables during the study were also recorded. The differences in density across housing complexes and the three types of wood were tested using ANOVA and continued with Duncan's test. The results showed three species of termites attacked wood baits, namely Microtermes insperatus, Macrotermes gilvus, and Odontotermes javanicus, all belong subterranean termite group. M. insperatus and O. javanicus had specific spatial distribution without overlapping zone among the two, while M. gilvus was the most adaptable and widely distributed in all housing complexes (<100-300 m asl.) regardless of the durable quality of the wood. There was significant difference in termite attacks across housing complexes with Ketapang housing complex in Sokaraja Subdistrict (<100 m asl.) was most frequently attacked. Conversely, there were no significant differences in termite attacks across the three types of wood (i.e. albasia, bangkirai, and teak).